5x+5x=-6+1+6x+3x

Simple and best practice solution for 5x+5x=-6+1+6x+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+5x=-6+1+6x+3x equation:


Simplifying
5x + 5x = -6 + 1 + 6x + 3x

Combine like terms: 5x + 5x = 10x
10x = -6 + 1 + 6x + 3x

Combine like terms: -6 + 1 = -5
10x = -5 + 6x + 3x

Combine like terms: 6x + 3x = 9x
10x = -5 + 9x

Solving
10x = -5 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
10x + -9x = -5 + 9x + -9x

Combine like terms: 10x + -9x = 1x
1x = -5 + 9x + -9x

Combine like terms: 9x + -9x = 0
1x = -5 + 0
1x = -5

Divide each side by '1'.
x = -5

Simplifying
x = -5

See similar equations:

| 10y-2=8y-1 | | 36a=32 | | 6x-9=24/18 | | 9r^2+12r-4=0 | | -y=2(0)-8 | | -y=2(2)-8 | | 215-5x=31x+19 | | 15(-2)-16=5y+9 | | 3/4(20a+12)+1/4(20a+12) | | 5-(x+6)=0 | | 15(0)-16=5y+9 | | 15(2)-16=5y+9 | | 5x+23=14x-23 | | 3x+8y=16 | | 0=-7 | | 5c/9c^6 | | 2=-7 | | f(10)=50-2x | | -7x-3=9 | | -7x-3=19 | | 10-7x=1+2x | | -7x-3=10 | | m+8.5=13.7 | | 16=8(-2)-4y | | 16=8(0)-4y | | 15a=6a+108 | | 5p-2p+4p= | | 16=8(2)-4y | | y=2*-1+(-2) | | 0=3 | | 60=3w^2 | | -(-2)-2=y |

Equations solver categories